The precision interventions for severe and/or exacerbation-prone asthma (PrecISE) adaptive platform trial: statistical considerations. Issue 6 (1st November 2020) - Ivanova, Anastasia; Israel, Elliot; LaVange, Lisa M.; Peters, Michael C.; Denlinger, Loren C.; Moore, Wendy C.; Bacharier, Leonard B.; Marquis, M. Alison; Gotman, Nathan M.; Kosorok, Michael R.; Tomlinson, Chalmer; Mauger, David T.; et al.
ABSTRACT: The Precision Interventions for Severe and/or Exacerbation-prone Asthma (PrecISE) study is an adaptive platform trial designed to investigate novel interventions to severe asthma. The study is conducted under a master protocol and utilizes a crossover design with each participant receiving up to five interventions and at least one placebo. Treatment assignments are based on the patients' biomarker profiles and precision health methods are incorporated into the interim and final analyses. We describe key elements of the PrecISE study including the multistage adaptive enrichment strategy, early stopping of an intervention for futility, power calculations, and the primary analysis strategy.